A simultaneous multi‐slice T2 mapping framework based on overlapping‐echo detachment planar imaging and deep learning reconstruction. Issue 5 (11th January 2022) - Li, Simin; Wu, Jian; Ma, Lingceng; Cai, Shuhui; Cai, Congbo
Abstract : Purpose: Quantitative MRI (qMRI) is of great importance to clinical medicine and scientific research. However, most qMRI techniques are time‐consuming and sensitive to motion, especially when a large 3D volume is imaged. To accelerate the acquisition, a framework is proposed to realize reliable simultaneous multi‐slice T2 mapping. Methods: The simultaneous multi‐slice T2 mapping framework is based on overlapping‐echo detachment (OLED) planar imaging (dubbed SMS‐OLED). Multi‐slice overlapping‐echo signals were generated by multiple excitation pulses together with echo‐shifting gradients. The signals were excited and acquired with a single‐channel coil. U‐Net was used to reconstruct T2 maps from the acquired overlapping‐echo image. Results: Single‐shot double‐slice and two‐shot triple‐slice SMS‐OLED scan schemes were designed according to the framework for evaluation. Simulations, water phantom, and in vivo rat brain experiments were carried out. Overlapping‐echo signals were acquired, and T2 maps were reconstructed and compared with references. The results demonstrate the superior performance of our method. Conclusion: Two slices of T2 maps can be obtained in a single shot within hundreds of milliseconds. Higher quality multi‐slice T2 maps can be obtained via multiple shots. SMS‐OLED provides a lower specific absorption rate scheme compared with conventional SMS methods with a coil with only a single receiver channel. The new method is of potential in dynamic qMRI and functional qMRI where temporal resolution is vital.